2012
DOI: 10.1007/s00701-012-1325-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up results in 142 adult patients with moyamoya disease according to management modality

Abstract: Revascularization surgery was effective in further ischemic stroke prevention to a statistically significant extent. Direct and combined bypasses were more effective to prevent recurrent ischemic stroke than indirect bypass. However, there is still no clear evidence that revascularization surgery significantly prevents rebleeding in adult MMD patients. More significant angiographic changes were observed in direct and combined bypasses compared with indirect bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 40 publications
5
48
1
Order By: Relevance
“…However, because revascularization using the indirect procedure often results in insufficient revascularization in adults, the direct/combined procedure has been increasingly used. 1,2,6,9,14,15,26,39,44 A limitation of this study was its retrospective nature. Because our surgical procedure also includes several steps of the indirect procedure (inverting dura matter, suturing temporalis muscle to the dura, and the placement of the pericranial flap), the result cannot be simply interpreted as a direct comparison between the direct STA-MCA bypass and indirect procedure alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, because revascularization using the indirect procedure often results in insufficient revascularization in adults, the direct/combined procedure has been increasingly used. 1,2,6,9,14,15,26,39,44 A limitation of this study was its retrospective nature. Because our surgical procedure also includes several steps of the indirect procedure (inverting dura matter, suturing temporalis muscle to the dura, and the placement of the pericranial flap), the result cannot be simply interpreted as a direct comparison between the direct STA-MCA bypass and indirect procedure alone.…”
Section: Discussionmentioning
confidence: 99%
“…21 Revascularization surgery is effective for improving symptoms and reducing the incidence of subsequent ischemic stroke in patients with ischemic MMD. 23 Whether revascularization surgery is helpful for preventing future intracranial hemorrhaging remains unclear. 17 Some studies have shown that patients who undergo revascularization surgery generally have a lower risk of rebleeding compared with those who undergo conservative treatment, but this difference is not statistically significant.…”
mentioning
confidence: 99%
“…17 Some studies have shown that patients who undergo revascularization surgery generally have a lower risk of rebleeding compared with those who undergo conservative treatment, but this difference is not statistically significant. 11,17,23 Patients with MMD are known to exhibit impairments in some cognitive functions, especially executive functions. 13,16,19,29,30,34 For example, Karzmark et al assessed executive function in 30 patients with MMD by examining the total number of correct responses on the Delis-Kaplan Executive Functioning System Design Fluency Test, Letter and Category Fluency Tests, and part B of the Trail Making Test and found that some of these patients had impaired executive functioning.…”
mentioning
confidence: 99%
“…[3101821] The same approach for reduction in risk of recurrent hemorrhage is less well established and debated, although the efficacy, particularly for combined bypass, has been reported. [6815] Management of aneurysms arising from deep collateral perforating vessels, however, poses a specific challenge and reports regarding their management are scarce. As with any aneurysm, definitive and rapid obliteration is desirable to avoid recurrent or incident hemorrhage, but direct surgical obliteration is generally difficult or may risk ischemia through obliteration of the associated collateral vessels.…”
Section: Introductionmentioning
confidence: 99%